Tadpole and vocalizations of Chiasmocleis hudsoni (Anura, Microhylidae) in Central Amazonia, Brazil - Rodrigues, Domingos J.; Menin, Marcelo; Lima, Albertina P.; Mokross, Karl S. (Zootaxa, 2008)
The genus Chiasmocleis is distributed from Panama to southern South America and contains 21 recognized species (Frost 2007). Eight of them are associated with Amazonian rainforests (Frost 2007). However, only the larvae of four species and the vocalization of three species have been described for species occurring in this region (Nelson 1973; Duellman 1978; Zimmerman & Bogart 1988; Hero 1990; Schlüter & Salas 1991; Lescure & Marty 2000; Vera Candioti 2006). The tadpole of C. hudsoni has not been formally described; it was mentioned briefly (diagrammatic drawings and larval color notes) in Hero´s tadpole identification key from Central Amazonia (Hero 1990), as Chiasmocleis cf. ventrimaculata. In this paper we describe the tadpole and the vocalizations of C. hudsoni and also provide comments on the spawning sites, clutch size and breeding periods.